2010
DOI: 10.1007/s00784-010-0412-z
|View full text |Cite
|
Sign up to set email alerts
|

Bone crestal height and bone density after third-molar extraction and grafting: a long-term follow-up study

Abstract: The objective of this study was to evaluate the long-term influence of xenogenic grafts on bone crestal height and radiographic density following extraction of teeth. The right and left third lower molars of 22 patients were surgically extracted, and one randomly chosen socket was filled with a xenogenic graft (Gent-Tech). The contralateral molar was left to heal naturally, serving as a paired control. Digital intraoral radiographies were taken at surgery and 2, 6, and 24 months after, to evaluate bone density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 9 publications
0
16
1
Order By: Relevance
“…Po.6 m was chosen because the major part of periodontal healing occurs within 3 months after surgery [ 9 ]. The mean reduction in the DBD depth was 1.28 ± 1.24 mm, which is slightly higher than that documented in other studies (0.62–1.25 mm) [ 4 , 6 , 13 ]. Hence, the root complex did not disturb periodontal healing of the M2M.…”
Section: Discussioncontrasting
confidence: 62%
“…Po.6 m was chosen because the major part of periodontal healing occurs within 3 months after surgery [ 9 ]. The mean reduction in the DBD depth was 1.28 ± 1.24 mm, which is slightly higher than that documented in other studies (0.62–1.25 mm) [ 4 , 6 , 13 ]. Hence, the root complex did not disturb periodontal healing of the M2M.…”
Section: Discussioncontrasting
confidence: 62%
“…In addition, bone density was also improved in the IBB group similar to that found in previous studies. [ 22 25 31 32 ] However, we cannot confirm that exists a more calcified tissue into the 3M defect due to the presence of the bone substitute that was not resorbed in a 1 year follow-up. [ 20 ] To verify the quantity and quality of new bone formation, it would require a histological evaluation of the graft, however, according to Sammartino et al .,[ 25 ] bone biopsy in this region should not be done by the bioethics principles since that a second surgical procedure on the graft area is unnecessary.…”
Section: Discussionmentioning
confidence: 95%
“…Other study claimed bone grafting did not have effect on MBL loss after two years, however, preoperative MBL loss was less than 2 mm both in control and grafted groups. [20]. It may enforce the observation that alveolar preservation is not necessary when preoperative MBL loss is less than 3 mm.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid it alveolar preservation with bone grafts or guided tissue regeneration may be considered, although MBL loss is not always significant after third molar removal [18,19]. Another study observed bone grafting has beneficial effect on MBL at the distal site of second molar, although MBL loss does not increase after six months when alveolar preservation was not applied [20]. It needs to be emphasized that periodontal pocket formation should be prevented when third molar removal is necessary.…”
Section: Introductionmentioning
confidence: 99%